Influence of low dietary histamine on the seizure development of chemical kindling induced by pentylenetetrazol in rats - JIN Chun-lei; SAKURAI Eiko; KISO Yoshinobu; LUO Jian-hong; YANAI Kazuhiko; CHEN Zhong (Acta Pharmacologica Sinica, 2016)
Aim: To determine the role of dietary low histamine on the seizure development of pentylenetetrazol (PTZ)-induced kindling in rats. Methods: After 14 d of feeding on a low histamine diet (LH, containing 0.145 μmol/g of histamine), the rats were chemically kindled by repeated intraperitoneal injection of a subconvulsant dose of PTZ (35 mg/kg) once every 48 h, and seizure activity of kindling was recorded for 30 min. Histamine in brain samples was analyzed using a high performance liquid chromatography system with a fluorescence spectrofluorometer. Results: The LH diet induced an increase in seizure response (seizure susceptibility) to the first trial of PTZ, and resulted in facilitation of subsequent PTZ kindling process (seizure development). The histamine levels in the cortex, hippocampus, and hypothalamus of LH-treated rats decreased significantly and these changes correlated well with seizure behavior (r = 0.875, 0.651, and 0.796, respectively). In addition, chronic kindled seizures resulted in a significant increase of the histamine content in the cortex and hypothalamus in the LH-fed groups. Conclusion: These findings indicate that the histamine in daily food could influence the brain histaminergic function, and play an important role in regulating seizure susceptibility.